Palmetto Profiles : the South Carolina encyclopedia guide to the South Carolina Hall of Fame - Emerson, W. Eric, 1966- (South Carolina encyclopedia guides., 2013)
Palmetto Profiles documents the lives and accomplishments of the inductees of the South Carolina Hall of Fame during its first forty years. As Governor John C. West predicted in his dedication speech, the Hall of Fame has indeed become a "vital and integral part of the history and culture of South Carolina." Nearly ninety citizens have been inducted since Apollo 16 astronaut Colonel Charles Duke, Jr., became the first honoree in 1973. Each year one contemporary and one deceased individual is recognized by the hall for outstanding contributions to South Carolina's heritage and progress. To date, inductees have included political leaders and reformers, artists, writers, scientists, soldiers, clergy, educators, athletes and others. U.S. President Andrew Jackson, authors Elizabeth Coker and Pat Conroy, jazz legend Dizzy Gillespie, artists Jasper Johns and Elizabeth O'Neil Verner, Catawba King Hagler, Generals Francis Marion and Thomas Sumter, civil rights leaders Mary McLeod Bethune and Reverend Benjamin E. Mays, U.S. Senators J. Strom Thurmond and Fritz Hollings, and Nobel Prize winning physicist Charles H. Townes are just some of the representative South Carolinians memorialized in the Hall of Fame for their lasting legacies in the Palmetto State and beyond. Published on the fortieth anniversary of the opening of the South Carolina Hall of Fame and drawn from biographical entries in The South Carolina Encyclopedia, this guidebook presents concise profiles of the inductees from 1973 to 2013. Palmetto Profiles, like the Hall of Fame itself, serves as a tangible link to South Carolina's rich and complex past to the benefit of residents, visitors and students alike. The volume also includes illustrations of all inductees and a foreword by Walter Edgar, a 2008 Hall of Fame inductee, author of South Carolina: A History and editor of The South Carolina Encyclopedia.